1964
DOI: 10.1182/blood.v23.5.669.669
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Fibrin Stabilizing Factor Activity in Various Diseases

Abstract: Ninety-five of 322 patients were found to have diminished plasma fibrin stabilizing factor (FSF) activity as measured by a modification of a threshold assay method. Repeat assays were normal in 85 of these 95 specimens after the addition of cysteine or other sulfhydryl-containing compounds to the plasma, suggesting that FSF was inactive in these instances. Abnormal specimens obtained from six patients with acute granulocytic leukemia, and three obstetrical patients with hypofibrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
19
0
2

Year Published

1967
1967
1978
1978

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(22 citation statements)
references
References 8 publications
1
19
0
2
Order By: Relevance
“…and stored at -220" C. until just before use. METHODS Factor-XI11 assays were performed according to Nussbaum and Morse (1964) Lysis experiments were performed in 13 x 99 mm. Lusteroid test tubes.…”
Section: Methodsmentioning
confidence: 99%
“…and stored at -220" C. until just before use. METHODS Factor-XI11 assays were performed according to Nussbaum and Morse (1964) Lysis experiments were performed in 13 x 99 mm. Lusteroid test tubes.…”
Section: Methodsmentioning
confidence: 99%
“…FSF has also been found to be low in acute as well as in chronic renal insufficiency (Nussbaum & Morse 1964, Mandalaki et a1 1970, Melissinos et al 1971. Low levels that became normal after addition of cystein to the test system have been found in patients with cancer (Nussbaum & Morse 1964).…”
mentioning
confidence: 96%
“…The studies have been carried out with various clot dissolution tests. The FSF level has been described as low in liver diseases (Nussbaum & Morse 1964, Walls & Losowsky 1969, Cucuianu et a1 1973. Some authors (Nussbaum & Morse 1964) ascribed this lowness to defective activation of FSF and found that the level became normal after addition of cystein to the test system.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Its activity is inhibited by SHinhibitors (Loewy & Edsell 1954), such as iodoacetamide (IAA), and transamidase inhibitors (Lorand et al 1966), such as glycinemethylester (GME). Inborn and acquired deficiencies of FSF activity are described (Duckert 1965, Nussbaum & Morse 1964.…”
mentioning
confidence: 99%